Hierarchical Modeling of the Thermal Insulation Performance of Novel Plasters with Aerogel Inclusions - Eugene D. Skouras; Georgia Tsolou; Alexandros N. Kalarakis (Energies, 2024)
Silica aerogel possesses a significantly lower thermal conductivity compared to still air at room temperature, thanks to its high porosity and advanced thermal and physical properties. It is extensively investigated for its potential use as an insulation material, usually being incorporated into other matrix materials, such as cement plasters, to enhance the overall thermal performance with minimal weight load. The development of lightweight thermal insulation materials is a key step in reducing energy consumption in hot and cold environments during construction and in thermal equipment. The superior insulation capabilities of aerogels stem from their nanostructured SiO2 framework, which induces nanoscale rarefaction effects on the enclosed air near the SiO2 structure. This study reconstructed the nanostructured SiO2 network of modern aerogels using microscopy imaging and the literature data and integrated it into sophisticated heat transfer simulations at a microscopic level to predict its thermal performance. The simulation assumed conduction as the primary energy dissipation mechanism, incorporating local rarefaction effects based on kinetic theory approaches. SiO2 aggregates were modeled as interconnected strings of spherical beads, with variations in the aggregate size explored in a parametric study. Nanoscale rarefaction phenomena, such as slip wall and Knudsen diffusion, prevalent at these grain sizes and structures, were incorporated to refine the modeling approach. The degree of the aerogel content relative to the effective properties of the multiphasic material was then investigated systematically along the multilayered mortar thickness and on a representative multiphasic layer at the mesoscopic level. The results quantify the significant decrease in the thermal conductivity of the heterogeneous material as the porosity of the aerogel increased. The insulation performance of this aerogel incorporated into cement plasters was assessed with this hierarchical approach and validated against experimental data, providing insights for the optimization of the fabrication process and potential applications in construction.